Customer satisfaction at Varsity Mall food court using quality function deployment method - Jamaludin, Muhammad Izzat Fahmi; Mohd Asaad, Mohd Norhasni (Universiti Utara Malaysia, 2020)
The purpose of this study is to measure customer satisfaction at Varsity Mall Food Court Universiti Utara Malaysia (UUM). The understanding of customer needs and satisfaction is very important in the design of products and services. This study applies "Quality Function Deployment (QFD)" a method widely used in industry to provide high quality goods and services according to the customers' specifications and the producers' limitations, to advising in a business department at a public university. Online questionnaires were distributed to School of Technology Managements and Logistics UUM students and out of 313 online questionnaires, 110 were returned with a response rate of 35.1%. The results from QFD show that the Varsity Mall Food Court UUM has the most convenient hour of operating is the most satisfied by the customer. However, most unsatisfied customers toward the Varsity Mall Food Court UUM has visually appealing material associated with the services. It is important for Varsity Mall Food Court UUM to understand customer needs and give priorities in terms of which dimension should they be focusing on improving their service.